IMPLEMENTATION OF THE POLICY OF REGIONAL EXPANSION IN NORTH MAMUJU REGENCY OF WEST SULAWESI - Syamsuddin Maldun (Indonesia Prime, 2016)
this study aims to: (1) Analyze and explain the stages of the implementation of the policy of regional expansion, and (2) analyze and explain the factors that support the implementation of the policy of regional expansion, in order to support national integration in North Mamuju Regency of West Sulawesi Province. This research is a kind of exploratory research using qualitative analysis approach. Data collection carried through; observation, interviews, and documents. Informant research include; Assistant I, II, III, Assistant to the Preparatory Committee the establishment of district (PPPK), head of the Central Bureau of statistics, the head of the Agency for the unity of the nation, the head of the Office library, Archives, and documents, the head of the Department of organization and Personnel, the head of the General section of the Secretariat of the Parliament, members of Religious Communication Forum (FKUB), the leadership of Dharma Wanita, professors, students, and community leaders. While the data analysis done in a descriptive qualitative. Technique of data analysis is interactive analysis: Data collection, (2) Data reduction, (3) Data Display, and (4) the Conclusion/verification. This is intended to give description in a systematic, factual and actual against objects that are examined. Research results show that; (1) the policy implementation stages of the extraction region North Mamuju Regency has been implemented in accordance with the legislation governing the extraction of such areas; the establishment of local governance devices, preparation of the vision and mission, the preparation of regional development strategies, and preparation of the regional development programs, and the factors that support the implementation of regional expansion policy is the existence of natural resources, capital investment (investment), infrastructure, transport and communications, openness toward outsiders, and support public (community)